2019
DOI: 10.1111/obr.12960
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and dental caries in early childhood: A systematic review and meta‐analyses

Abstract: Obesity and dental caries in children are significant health problems. The aims of this review are to identify whether children aged 6 years and younger with overweight and/or obesity have higher dental caries experience compared with children with normal weight and, secondly, to identify the common risk factors associated with both conditions. Medline, Embase, and seven other databases were systematically searched followed by lateral searches from reference lists, grey literature, theses, conference proceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 60 publications
2
113
1
3
Order By: Relevance
“…Similar trends were seen in periodontal diseases, although the results were not fully consistent at all follow-up appointments. However, these results are in keeping with 2 longitudinal studies in adolescents and young adults ( Li et al 2017 ; Oreskovic et al 2017 ) and meta-analyses ( Martens et al 2017 ; Manohar et al 2019 ). Key determinants of these associations are dietary risk factors, especially carbohydrate intake, but the mechanisms seem to differ between caries and periodontitis ( Chapple et al 2017 ).…”
Section: Discussionsupporting
confidence: 84%
“…Similar trends were seen in periodontal diseases, although the results were not fully consistent at all follow-up appointments. However, these results are in keeping with 2 longitudinal studies in adolescents and young adults ( Li et al 2017 ; Oreskovic et al 2017 ) and meta-analyses ( Martens et al 2017 ; Manohar et al 2019 ). Key determinants of these associations are dietary risk factors, especially carbohydrate intake, but the mechanisms seem to differ between caries and periodontitis ( Chapple et al 2017 ).…”
Section: Discussionsupporting
confidence: 84%
“…3 Perinatal factors may also play a role, and studies have examined possible associations between early childhood caries and preterm birth, low birth weight, childhood body mass index and the metabolic syndrome, all with conflicting results. [4][5][6][7] Preterm birth occurs before 37 completed weeks of gestation and the global incidence is 11%. 8 A systematic review and meta-analysis published in 2019 has addressed the association between preterm birth and low birth weight and early childhood caries.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has reported more than 100 unique biological, genetic, social and behavioural risk factors for early childhood caries in a complex interplay 3 . Perinatal factors may also play a role, and studies have examined possible associations between early childhood caries and preterm birth, low birth weight, childhood body mass index and the metabolic syndrome, all with conflicting results 4‐7 . Preterm birth occurs before 37 completed weeks of gestation and the global incidence is 11% 8…”
Section: Introductionmentioning
confidence: 99%
“…Також у 95,01 % дітей із хворобами ГБС виявлено ознаки гінгівіту. Науковці Manohar N, Hayen A, Fahey P, Arora A [18] установили, що діти з надмірною вагою й ожирінням мали значно більше уражених карієсом зубів, ніж діти з нормальною вагою, а також виявили низький рівень санітарної освіти батьків щодо харчування дітей і догляду за зубами.…”
Section: результати дослідженняunclassified